2017
DOI: 10.1136/thoraxjnl-2017-209967
|View full text |Cite
|
Sign up to set email alerts
|

Role of atmospheric pollution on the natural history of idiopathic pulmonary fibrosis

Abstract: This study suggests that air pollution has a negative impact on IPF outcomes, corroborating the role of ozone on AEs and establishing, for the first time, the potential role of long-term exposure to PM and PM on overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 36 publications
6
136
5
2
Order By: Relevance
“…Other studies using Cox proportional hazards model to evaluate the impact of air pollution on acute exacerbation (AE) or disease progression of IPF in longitudinal cohorts identified that onset of AE was significantly associated with antecedent 6-week increases in O 3 concentration [11]. Besides, mortality was significantly associated with increased levels of exposure to PM2.5 and PM10 [12]. Together, these epidemiological studies argue that air pollution has a negative impact on IPF incidence and outcomes; however, the underlying mechanisms that regulate these processes are still being uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using Cox proportional hazards model to evaluate the impact of air pollution on acute exacerbation (AE) or disease progression of IPF in longitudinal cohorts identified that onset of AE was significantly associated with antecedent 6-week increases in O 3 concentration [11]. Besides, mortality was significantly associated with increased levels of exposure to PM2.5 and PM10 [12]. Together, these epidemiological studies argue that air pollution has a negative impact on IPF incidence and outcomes; however, the underlying mechanisms that regulate these processes are still being uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of IPF is challenging and hard to foresee, but the slow gait speed in IPF could be a simple, reliable tool that may detect phenotypes associated with a worse clinical outcome. The efforts to better define the risk factors of IPF progression had led to the environmental analysis and a real association with air pollution and long‐term exposure to PM 10 and PM 2.5 linked to an increase of the mortality …”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Following the recent update on acute exacerbation (AEx) of IPF, there have been a number of further publications on the subject . Bronchoscopy assessment of AEx in a retrospective cohort of patients with varied ILD diagnoses did not provide benefit, with a positive yield of 13%, and a change in management in only 4 of 106 patients, while ICU transfer as a result of the procedure occurred in more than half of the patients .…”
Section: Interstitial Lung Diseasementioning
confidence: 99%